Comparison of Three Methods for Diagnosing Trichomoniasis in Female Patients with Sexual Activity Attended at a Hospital in Peru - Jaime Rosales-Rimache; Jorge L. Inolopú; Fernando C. Soncco-Llulluy; Leslie Medina-Ciprian (Journal of Parasitology Research)
Background. Trichomoniasis is a sexually transmitted infection that mainly affects women. The diagnosis is made by different methods that identify the presence of Trichomonas vaginalis; therefore, sensitivity, specificity, and performance are essential to guarantee an adequate diagnosis. Our study is aimed at comparing three methods for diagnosing trichomoniasis in patients treated at a hospital in Peru during the year 2018. Methods. We designed a cross-sectional study and enrolled women whose vaginal secretion samples were evaluated by direct examination, Papanicolaou staining, and culture in the Diamond medium. Results. We evaluated 134 women with a mean age of 36.6±12.1 years and a beginning of sexual activity of 18.5±3.0 years. We found leukocyte infiltration, fetid odor, and strawberry cervix in 66.4%, 35.1%, and 18.7%. The prevalence of trichomoniasis by the culture method, direct examination, and Papanicolaou was 32.1, 21.6, and 11.2%. The direct examination’s sensitivity, specificity, and diagnostic performance (AUC) were 65.1%, 98.9%, and 82.0%, while for the Pap smear, they were 32.6%, 98.9%, and 65.7%%. Conclusion. The culture of T. vaginalis is the gold standard for diagnosing trichomoniasis; however, direct examination is a fast, specific alternative with good diagnostic performance. The Pap test has low sensitivity and should not be used in settings where the prevalence and risk factors for trichomoniasis are high.